THE RHETORICAL STYLE OF INDONESIAN AUTHORS’ CITATION IN ENGLISH RESEARCH ARTICLES INTRODUCTIONS - Destiantari Adila (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Citation in introduction subsection in a research article is something that should be considered important by an author. The aim of this study is to analyze the way Indonesian authors rhetorically review prior knowledge in their research article introduction. This study focuses on (1) the analysis of type of citation mostly used by Indonesian author, (2) kind of tenses mostly used by Indonesian author, and (3) the ways Indonesian authors rhetorically review relevant prior knowledge in introduction subsection of their English research article published in International journals. The design of this study was descriptive qualitative. The results showed that (1) the type of citation mostly used by Indonesian authors was non-integral citation with percentage of 86.80%, (2) kind of tenses mostly used by the Indonesian authors was present tense with the percentage of 70.51% and then followed by present perfect tense 16.57% and finally past tense 12.92%, and (3) positive justification was the most dominantly used by Indonesian authors in reviewing relevant prior knowledge with the percentage of 37.92% and then followed by supporting research topic with the percentage 26.12%, and the percentage for question raising from the result of previous study was only 0.28%. It can be concluded that the way Indonesian authors writing research article is different from International authors.